Traditional isolation of fungal species in fish culture ponds - Duaa R.M. Al-Safi (The Bioscan, 2025)
Background: In Iraq, fish ponds have increasingly grown in last decade as important source of protein to maintaining of human healthy; however, contamination of water is a serious threat to aquaculture systems causing severe economic losses. Aim: Traditional identification of the main fungal pathogens in fish ponds existed in different areas in Wasit province (Iraq) Materials and methods: Totally, 148 water samples were collected equally from 37 fish ponds located in five main areas (Al-Kut, Al-Suwaira, Al-Aziziyah, Al-Numaniyah, and Al-Hay) in Wasit province (Iraq) during June-July (2024). Then, all samples were filtered, cultured using three different media; Sabouraud Cycloheximide Chloramphenicol Agar, Potato Dextrose Agar, and Malt Extract Agar, and the grown colonies of fungal isolates were purified and characterized morphologically and microscopically. Results: An overall 75.68% water samples and 83.78% of fish ponds were showed contaminated with at least one fungus. Regarding study areas, fungal contamination of water samples was increased significantly in Al-Hay and decreased significantly in Al-Numaniyah and Al-Suwaira; whereas in fish ponds of study areas, significant increases of fungal contamination was shown in Al-Aziziyah, Al-Numaniyah, Al-Hay, and Al-Kut; but decreased in Al-Suwaira. Also, a total of 12 different species and genera were detected among the study samples, which involving 382 fungal colonies; in which, significant increases were reported in Aspergillus niger and Penicillium sp.; while significant decreases were seen in Trichophyton mentagrophytres, Helminthosporium sp., Mucor sp., and Trichoderma sp. when compared to values of other fungal colonies; Cladosporium sp., Rhizopus stolonifer, Microsporium cani, Fusarium solani, Candida albicans, and Alternaria alternate. Among study areas, significant increases of fungal colonies were detected in Al-Kut and reduced in Al-Aziziyah. In relation to each area, significant increases in percentage of fungal colonies were seen in Helminthosporium sp. in Al-Kut; Alternaria alternate in Al-Suwaira; Trichophyton mentagrophytres in Al-Aziziyah; Trichoderma sp. in Al-Numaniyah; and Fusarium solani and Microsporium cani in Al-Hay. Conclusions: Our findings revealed the presence of apparent fungal contamination in fish ponds existed in Wasit province suggesting the importance of national studies to investigating and controlling the fungal contamination and their diseases to ensure continued high-quality growth of fish in aquaculture production industry.